1990
DOI: 10.2118/90-06-02
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behaviour And Physical Properties Of Lindbergh Heavy Oil/CO2 Mixtures

Abstract: The objective of this work is to acquire phase behaviour and physical property data of carbon dioxide/heavy oil systems pertaining ta enhanced oil recovery by CO2 huff-n-puff and steam stimulation. Phase behaviour and physical property measurements were carried out on Lindbergh heavy oil CO2 mixtures at 21 °C and 140 °C, and at pressures ranging up to about 15 MPa. Furthermore, the oil samples were analyzed using gas chromatographic simulated distillation. The experimental measurements were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…An example is Chuang et al, where the CO2 solubility, oil swelling factor and viscosity for 4 different CO2 saturated heavy crude oils were measured and correlated at different temperatures and pressures [4]. Similar studies can also be found in [5][6][7][8][9][10][11]. In addition, the viscosity of CO2 and alkane diluted crude oil was reported by Li et al [12].…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…An example is Chuang et al, where the CO2 solubility, oil swelling factor and viscosity for 4 different CO2 saturated heavy crude oils were measured and correlated at different temperatures and pressures [4]. Similar studies can also be found in [5][6][7][8][9][10][11]. In addition, the viscosity of CO2 and alkane diluted crude oil was reported by Li et al [12].…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, as reported by many papers [6][7][8][9]15], CO2 solubility in crude oil normally increases with increasing pressure but decreases with increasing temperature. The pressure sensitivity of the CO2 solubility at high pressures depends on the phase of CO2: when CO2 is in the liquid phase, the solubility is least sensitive to pressure [4,7].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations